2021
DOI: 10.1155/2021/5816837
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Is a Promising Method to Restore Gut Microbiota Dysbiosis and Relieve Neurological Deficits after Traumatic Brain Injury

Abstract: Background. Traumatic brain injury (TBI) can induce persistent fluctuation in the gut microbiota makeup and abundance. The present study is aimed at determining whether fecal microbiota transplantation (FMT) can rescue microbiota changes and ameliorate neurological deficits after TBI in rats. Methods. A controlled cortical impact (CCI) model was used to simulate TBI in male Sprague-Dawley rats, and FMT was performed for 7 consecutive days. 16S ribosomal RNA (rRNA) sequencing of fecal samples was performed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 81 publications
3
60
0
Order By: Relevance
“…Interestingly, vagal stimulation reduced gut barrier permeability after TBI, mediated by the suppression of TNF-a release (106). Recently, it has been demonstrated that FMT can restore gut microbiota dysbiosis following TBI and ameliorate neurological deficits, mediated by the TMA-TMAO-MsrA signaling pathway (96).…”
Section: Wdi Micementioning
confidence: 99%
“…Interestingly, vagal stimulation reduced gut barrier permeability after TBI, mediated by the suppression of TNF-a release (106). Recently, it has been demonstrated that FMT can restore gut microbiota dysbiosis following TBI and ameliorate neurological deficits, mediated by the TMA-TMAO-MsrA signaling pathway (96).…”
Section: Wdi Micementioning
confidence: 99%
“…The direct cause of tissue damage following TBI is the increase of local oxygen free radicals and the occurrence of stress oxidation reaction. Among them, ROS and MDA are directly involved in brain damage and excessive release of excitatory neurotransmitters ( 30 ). Following TBI, the levels of ROS and MDA rise sharply, while the activities of biological enzymes that scavenger oxygen free radicals, such as SOD and CAT, remain basically unchanged ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gut-dysbiosis-induced neuroinflammation seems to be at least partially mediated by microglia and astrocytes, which have also been shown to be regulated by enteric metabolites [ 54 , 61 , 64 ]. Restoration of healthy microbiota can interrupt this process and improve neurological deficits after TBI [ 76 ]. Consistent with the general model of the gut–brain axis, SCFA metabolism seems to be a critical element of TBI-induced gut dysbiosis.…”
Section: Mechanisms Of Microbiome Disruption In Neurologic Diseasementioning
confidence: 99%